2017
DOI: 10.1007/s10902-017-9945-z
|View full text |Cite
|
Sign up to set email alerts
|

How Does Life Satisfaction Change During the Transition from School to Work? A Study of Ninth and Tenth-Grade School-Leavers in Germany

Abstract: Weber, E., & Hülür, G. (2021). Co-development of couples' life satisfaction in transition to retirement: A longitudinal dyadic perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
3
7
0
Order By: Relevance
“…Overall, findings indicate that leaving school was positive for health and well-being, irrespective if participants entered a prevocational program, vocational training, university, employment or inactivity after school. Two other studies from Finland and Germany found similar results for subjective well-being [ 28 , 49 ]. Accordingly, a study from Canada observed decreases in the prevalence of depression during the same time period [ 50 ].…”
Section: Discussionsupporting
confidence: 69%
“…Overall, findings indicate that leaving school was positive for health and well-being, irrespective if participants entered a prevocational program, vocational training, university, employment or inactivity after school. Two other studies from Finland and Germany found similar results for subjective well-being [ 28 , 49 ]. Accordingly, a study from Canada observed decreases in the prevalence of depression during the same time period [ 50 ].…”
Section: Discussionsupporting
confidence: 69%
“…However, from a closer institutional perspective, Salmela‐Aro and Tuominen‐Soini (2010) analyze Finnish data and show that life satisfaction increases during school transitions from comprehensive education to an academic or vocational track. Siembab and Stawarz (2019) find increasing levels of life satisfaction after individuals leave comprehensive school, regardless of occupational status or vocational track. Similarly, Dockery (2010) reports that successful transitions from school to work (e.g., the transition from secondary to post‐secondary education) have a positive impact on happiness.…”
Section: School‐to‐work Transition and Life Satisfactionmentioning
confidence: 99%
“…Research focusing on the development of subjective well‐being during the transition from youth to young adulthood shows that subjective well‐being decreases during this period (e.g., Baird et al., 2010; Beatton & Frijters, 2012; Burger & Samuel, 2017; Herke et al., 2019; Wunder et al., 2013). Furthermore, transition‐centered studies indicate that transitions to post‐compulsory education are positively related to subjective well‐being (Salmela‐Aro & Tuominen‐Soini, 2010; Siembab & Stawarz, 2019). Moreover, research investigating the associations between different transition statuses shows that young individuals enrolled in post‐compulsory education are happier than young individuals who work (Dockery, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, this apparent negative effect of an AAG on mental health disappeared when differences in depressive symptoms associated with educational attainment were additionally controlled for (Reynolds & Baird, 2010). Likewise, a recent study of German adolescents did not find differences in life satisfaction between those who experienced an educational AAG and those who did not (Siembab & Stawarz, 2019).…”
Section: Previous Research On the Consequences Of Occupational Aags For Swbmentioning
confidence: 88%
“…Thus, the findings of these few studies are not readily generalizable to the potential consequences for SWB of an early career AAG in the highly structured German school and VET system. In addition, these studies were mostly cross-sectional and did not investigate how SWB developed over time as a function of an AAG (for exceptions, see Siembab & Stawarz, 2019;Smith & Frank, 2005). Some of the studies also looked at quite different outcomes (e.g., [mental] health rather than SWB) or used only global measures of SWB.…”
Section: Previous Research On the Consequences Of Occupational Aags For Swbmentioning
confidence: 99%